TRAF3: Uncovering the Real but Restricted Role in Human - BOWIE, ANDREW (My University, 2010)
In this issue of Immunity, Perez de Diego et al. (2010) report a primary human immune deficiency involving a TRAF protein, and show that human immunity to the virus HSV-1 is critically dependent on TRAF3.
PUBLISHED
Keywords: TRAF3; Immunology, Inflammation & Infection